2008
DOI: 10.1080/14756360701342581
|View full text |Cite
|
Sign up to set email alerts
|

Effects of some antibiotics on human erythrocyte glutathione reductase: anin vitrostudy

Abstract: Inhibitory effects of some antibiotics on purified human erythrocyte glutathione reductase were investigated. Human erythrocyte glutathione reductase was purified 2800-fold (29% yield) at 48C using 2 0 , 5 0 -ADP Sepharose 4B affinity gel and Sephadex G-200 gel filtration chromatography. SDS polyacrylamide gel electrophoresis showed a single band for the enzyme. Imipenem, rifamycin, sulfanylacetamide, ceftazidime, chloramphenicol, seftriaxon, vancomycin, cefuroxime and ornidazole exhibited inhibitory effects b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 23 publications
0
30
0
1
Order By: Relevance
“…The resultant solution was clear, and contained partially purified enzyme. Then it dialysed at 48C in 1 mM EDTA þ 10 mM K-phosphate buffer (pH 7.5) for 2 h with two changes of buffer [16]. Partially purified enzyme solution was kept at 48C.…”
Section: Ammonium Sulphate Precipitationmentioning
confidence: 99%
See 3 more Smart Citations
“…The resultant solution was clear, and contained partially purified enzyme. Then it dialysed at 48C in 1 mM EDTA þ 10 mM K-phosphate buffer (pH 7.5) for 2 h with two changes of buffer [16]. Partially purified enzyme solution was kept at 48C.…”
Section: Ammonium Sulphate Precipitationmentioning
confidence: 99%
“…Active fractions were collected and dialyzed with equilibration buffer. All of the procedures were performed at 48C [16].…”
Section: Ammonium Sulphate Precipitationmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies found either increases or decreases in mammalian enzyme activities, and the inhibitor or activator effects of some antibiotics have been rarely investigated. Nevertheless, a few recent investigations regarding the inhibitory actions of different type of drugs and chemicals on GR have been reported by our group [9][10][11][12][13][14][15] . Cefuroxime is a second-generation cephalosporin antibiotic whereas ceftriaxone, ceftizoxime and cefoperazone are third-generation cephalosporin antibiotics.…”
Section: Introductionmentioning
confidence: 99%